BACKWARD CHAINING METHOD UNTUK DIAGNOSA PENYAKIT BINTIK MERAH PADA KULIT BAYI MENGGUNAKAN APLIKASI BERBASIS WEB - Lilis Nur Hayati; Yulita Salim; Hasriwiani Habo Abbas; Rezky Anugrah; Herawati Herawati; Ihwana As'ad; Muflih Awaluddin (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2023)
Weak immunity or the baby's immune system makes it very susceptible to bacteria, germs and disease. Babies have difficulty explaining their complaints, therefore parents are expected to catch every body language from their child. In general, if a child has health problems, parents will check with a health service provider and consult with health workers who are experts in their field, but sometimes there are obstacles such as limited working hours (practice). So in this study a tool was created in the form of a website-based expert system to diagnose red spots in babies using the Backward Chaining method. The Backward Chaining method searches with the goal first followed by a description of the attributes in this case, namely the disease first and then adjusted to the existing symptoms. The system uses the waterfall method, The results of this study show that an expert system can properly diagnose red spots on the baby's skin to help parents identify and find appropriate treatment solutions. Testing this system can be understood and implemented with the value of application users obtaining an assessment of 81% agreeing according to baby's parents, nurses and dermatologists.